Maternal plasma levels of vitamin D in postterm pregnancy. (18th August 2022) - Erdoğan, Kadriye; Sanlier, Nazlı Tunca; Çelik, Bülent; Arslan, Burak; Diktaş, Gülşah; Yücel Çelik, Özge; Köse, Caner; Engin-Üstün, Yaprak
Abstract: This study was conducted to examine the levels of vitamin D in postterm pregnancy. The study consisted of two groups: Group 1: women with postterm pregnancy in whom labour has not started ( n = 40). Group 2: pregnant women with spontaneous labour between 37 and 41 weeks of gestation ( n = 40). Demographic characteristics of individuals, age, body mass index, gravida, parity, living child, number of abortions and birth characteristics were recorded. Prepartum and postpartum haemoglobin (Hb) and haematocrit (Hct) values ​​and vitamin D levels of pregnant women were measured. We found no significant differences in vitamin D levels, smoking, mode of delivery, induction of labour, methods of cervical ripening and maternal and perinatal complications between the groups ( p > .05). D vitamin in the model had a statistically significant effect on prepartum Hb ( p < .05). Vitamin D levels seem not to be associated with postterm pregnancy. Vitamin D had a statistically significant effect on prepartum Hb. IMPACT STATEMENT: What is already known on this subject? The aetiology of post term pregnancy is not clearly known, factors such as foetal anencephaly, foetal sex, placental sulfatase deficiency, genetic factors, and high pre-pregnancy body mass index play a role. What do the results of this study add? Vitamin D levels seem not to be associated with postterm pregnancy. Vitamin D had a statistically significant effect on prepartum Hb. What are the implications of these findings for clinical practice and/or further research? Further studies are needed to clarify the relationship between vitamin D levels and postterm pregnancy.